Knowledge and attitude regarding organ donation and transplantation among undergraduate medical students in North coastal Andhra Pradesh - Ganta, Srinivas Rao; Pamarthi, Kiran; K. K., Lakshmi Prasad (International Journal Of Community Medicine And Public Health, 2018)
Background: Organ transplantation is one of the greatest scientific advances and remains one of the most challenging and complex field of modern medicine. In the USA and UK, the organ donation rate is 26 and 14 per million, whereas in India, it is only 0.34 per million population. Healthcare professionals act as the critical link in the organ procurement process because they are the first individuals to establish relationship with the potential donors’ family. Methods: An institution based descriptive cross-sectional study was conducted among first year undergraduate medical students during November 2017. Convenient sampling method was used to obtain the sample size. Out of 150 students in first year, 136 students fulfilling the inclusion and exclusion criteria were studied. Results: Out of 136 students who participated in the study, 58 (42.6%) were boys and 78 (57.4%) were girls. All the 136 (100%) students had heard about organ donation, but only 24 (17.6%) of them were aware of organ donation associations. Very few students (5, 3.6%) know about any law related to organ donation in India. Mass media like TV, Internet and Newspapers have played a major role in imparting awareness regarding organ donation among students besides relatives and friends. Majority of the students i.e. 104 (76.4%) were ready to donate their organs if need comes and two third of them accepted that they would allow organ donation from a member of their family after Brainstem death. Conclusions: There is a positive attitude of medical students towards organ donation but there is lack of sufficient knowledge on the topic. Improving their knowledge by including organ donation topic in medical curriculum can help to reduce this gap.